Upaya Pendidikan Islam dalam Pengembalian Kurikulum Salaf (Studi Kasus di Madrasah Muallimin Tebuireng) - Yusuf Yusian Septianto Saleh; Lukman Hakim (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
Educational institutions are an institution or organization engaged in the field of education as a place or place for the process of planning, managing and supervising education that aims to help and develop the intelligence of students and the components involved in it. In educational institutions there are various kinds of elements that form a unity and influence each other, such as from curriculum, human resources, financial institutions, and leadership from a school principal or madrasa. In relation to the research being conducted, the focus of the research is on: 1) The background underlying the establishment of Madrasah Muallimin Hasyim Asy'ari Tebuireng Jombang, 2) Efforts to restore the Salaf curriculum, 3) The process of developing the Salaf curriculum. This research is included in qualitative research. This research model uses the Snowball technique which is one of the research processes. Observations and interviews are the subject of research because the source of data from researchers, uses interviews that are accompanied by observations in the field to obtain data that is valid and in accordance with reality. By involving the founders of the madrasa, the head of the madrasa, the deputy head of the curriculum and the deputy head of the student field as the research resource. This research was conducted at the Madrasah Muallimin Hasyim Asy'ari Tebuireng Jombang. Madrasah Muallimin is the answer from the Tebuireng Islamic Boarding School which is considered to have lost the Salaf curriculum material, so researchers are interested in what is the background and the history of Muallimin School. the establishment that was nurtured by KH Hasyim Asy'ari. In the results of this study, it is known several things related to the focus of research; first, the purpose of the establishment of the Madrasah Muallimin Tebuireng; second, in the effort to return the Salaf curriculum, it is known the process of returning the Salaf curriculum, the implementation of the Salaf curriculum, the Salaf curriculum management and the Salaf curriculum component; third, in the process of developing the Salaf curriculum, it is known that the Salaf Islamic Boarding School education system, the role of education staff, the management of the headmaster in the development of the Salaf curriculum, and the foundation of the quality of the Salaf curriculum. In the discussion it was concluded that the efforts of educational institutions in returning the Salaf curriculum at Madrasah Muallimin Tebuireng aimed to restore the Salaf curriculum which had been lost due to the existence of a general curriculum. Efforts were made, namely by gathering senior alumni and senior kyai to form an educational unit to continue the struggle of KH. Hasyim Asy'ari. As for the process of developing the Salaf curriculum, it uses a system approach model and a comprehensive approach model